2018
DOI: 10.13004/kjnt.2018.14.2.93
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of Subdural Hygroma after Decompressive Craniectomy

Abstract: ObjectiveSubdural effusion, also known as subdural hygroma (SDG), is a secondary complication that can occur after decompressive craniectomy (DC). However, the pathogenesis of SDG is not fully understood. It is unclear whether SDG occurrence is related to preoperative patient status or surgical technique. The purpose of this study is to identify risk factors for SDG after DC.MethodsFifty-nine patients who underwent DC from January 2016 to December 2016 at the same institution were analyzed. We retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(41 reference statements)
0
8
0
1
Order By: Relevance
“…Many studies have indicated that age is not a risk factor for patients with severe TBI who have undergone decompressive craniectomy ( 6 , 7 , 11 ). However, studies have shown that older patients are prone to subdural effusion for without decompressive craniectomy ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have indicated that age is not a risk factor for patients with severe TBI who have undergone decompressive craniectomy ( 6 , 7 , 11 ). However, studies have shown that older patients are prone to subdural effusion for without decompressive craniectomy ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the formation of TSE has a greater impact on the prognosis of patients has yielded different conclusions in numerous studies. In a study by Kim et al ( 7 ), it was believed that the occurrence of TSE was unrelated to a patient's prognosis, as it only prolongs the patient's hospital stay. However, in another study ( 5 ), TSE was divided into four types according to different clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shunt surgeries were performed in the patients; who showed progressively enlarged ventricles with deteriorating or failures in improvement of neurologic state; who were not tolerable to gradual reduction of amount of CSF drainage. For patients who were treated with craniectomies, the size of the craniectomy was approximated using the formula for an ellipse : AB/4, where A is the longest anterior-posterior length as determined on the axial CT cuts, and B is calculated using CT slice thickness and the number of axial cuts containing the craniotomy [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Decompressive craniotomy or craniectomy is performed if there is no response to medical therapy in the increased intracranial pressure state. However, many complications may occur following the procedure [1,2]. Remote acute subdural hematoma (ASDH) following a decompressive craniotomy or craniectomy is a rare phenomenon [3,4].…”
Section: Introductionmentioning
confidence: 99%